A review of efficient high productivity solar stills. (March 2019) - Arunkumar, T.; Raj, Kaiwalya; Dsilva Winfred Rufuss, D.; Denkenberger, David; Tingting, Guo; Xuan, Li; Velraj, R.
Abstract: Fresh water is an indispensable resource, which is getting contaminated. The shortage of freshwater has been identified as a crucial issue all around the world. Solar desalination is one of the options to produce fresh water from any type of contaminated water (brackish, contaminated and sea water) in a sustainable way. A solar still is a simple device used to purify the water using solar energy through evaporation and condensation processes. In general, the productivity of the conventional solar still (CSS) is about 2–5 l/m 2 /day. But this quantity is not sufficient for an individual to lead an adequate life. Hence either more than 1 m 2 is required per person or better yet are modifications to improve the yield of the fresh water (likely more than 5 l/m 2 /day). In this work, an attempt has been made to categorize the different solar still designs with productivity exclusively more than 5 l/m 2 /day. Here, we identify as such efficient high productivity stills and discuss their novel modifications and heat transfer mechanism to arrive at useful conclusions. This comprehensive review will be a reference guide for future researchers who wish to concentrate only on efficient high productivity solar stills to improve the productivity further. Highlights: All Innovative high productivity solar still designs are reviewed. Efficient high productivity solar stills with more than 5 l/m 2 /day is categorized. The maximum productivity designs are summarized.